Placing anurans in water can improve photo-based individual identification - Edina Nemesházi; Zsanett Mikó; Nikolett Ujhegyi; Andrea Kásler; Nadine Lehofer; Veronika Bókony (PLoS ONE, 2026)
Identification of individuals across time and space is required for investigating numerous evolutionary-ecology and conservation-related questions, and photo-based identification is commonly used for a broad taxonomic range. Success of available photo-matching software may greatly depend on image quality as well as the focal body parts. We tested the hypotheses that individual identification by colour patterns can be facilitated by taking into account the natural medium surrounding the animals and the natural body posture they tend to take. We optimised photography methods enabling individual identification by whole-body assessment of agile frogs (Rana dalmatina) , and compared the reliability of those photography methods for computer-assisted identification in the HotSpotter software as well as for observers operating it. We found that photographing either hand-restrained frogs with towel-dried skin, or frogs moving freely in clean water enabled comparison of the dorsal surface of the whole body including the hind legs, and HotSpotter identified matching images at rates similar to those anuran studies that reported high success before. Specifically, the true match ranked in the top 10 for >92% of photographs taken with the above methods. By contrast, submerging hand-restrained frogs in water significantly improved identification: images of the same individual were always ranked as the most likely match. We attribute this outstanding performance to the combination of advantageous effects of in-water light refractions that improve the visibility of pigment patterns, and uniform body postures facilitating comparison across individuals. Observers in general successfully identified matching images and ruled out non-matching ones, but some mistakes were recorded when images featured freely moving frogs. The photography methods described in this study should be easily adapted to most frog and toad species for reliable individual identification. Our study highlights that taking into account features of the natural environment of the studied species can improve individual identification by photographs.